1992
DOI: 10.1542/peds.89.4.619
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Problems During Child Health Supervision Visits: Eliciting,Then What?

Abstract: An explicit goal of child health supervision visits is to gather information and provide guidance about the psychosocial problems of children and families. The purpose of this study was to determine the extent to which parents had opportunities to express psychosocial concerns and the nature of physicians' responses to these concerns during health supervision visits. The authors analyzed videotapes of child health supervision visits by 34 children aged 5-12 years to 34 pediatric and family medicine residents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In contrast, universal screening provides pediatricians with relevant parent-reported information without pediatricians having to elicit concerns or parents having to initiate conversations, thus improving pediatricians' ability to detect problems across all children and potentially reduce disparities in care. Moreover, while one study found that 17% of providers ignored parentraised concerns about child behavior during well-child visits (Sharp, Pantell, Murphy, & Lewis, 1992), another study found an increase in parents who reported that their provider talked about their concerns and that their questions were answered following screening (Schonwald, Horan, & Huntington, 2009).…”
Section: Pediatrician's Assessment Of Child Mental Health Problemsmentioning
confidence: 99%
“…In contrast, universal screening provides pediatricians with relevant parent-reported information without pediatricians having to elicit concerns or parents having to initiate conversations, thus improving pediatricians' ability to detect problems across all children and potentially reduce disparities in care. Moreover, while one study found that 17% of providers ignored parentraised concerns about child behavior during well-child visits (Sharp, Pantell, Murphy, & Lewis, 1992), another study found an increase in parents who reported that their provider talked about their concerns and that their questions were answered following screening (Schonwald, Horan, & Huntington, 2009).…”
Section: Pediatrician's Assessment Of Child Mental Health Problemsmentioning
confidence: 99%
“…Parents are most likely to seek professional behavioral guidance from their child’s PCP (Taylor, Moeller, Hamvas, & Rice, 2013). As a result, behavioral concerns are raised in 50–80% of all child medical visits (Cassidy & Jellinek, 1998; Fries et al, 1993; Sharp et al, 1992) and are the primary presenting concern in 15–20% of cases (J. Williams, Klinepeter, Palmes, Pulley, & Foy, 2004).…”
Section: Why Study Routine Behavioral Issues?mentioning
confidence: 99%
“…There has long been a strong argument for the benefits of merging of pediatric medicine and behavioral science to promote behavioral health (Smith, Rome, & Freedheim, 1967). This argument has varied some over time, but it generally hinges on a few well-established findings: (a) child behavior problems are quite common in pediatric settings (Arndorfer, Allen, & Aljazireh, 1999; Cassidy & Jellinek, 1998; Fries et al, 1993; Sharp, Pantell, Murphy, & Lewis, 1992); (b) primary care providers (PCPs) face significant barriers to the provision of behavioral care, including limited time, inadequate training, and financial disincentive (Cooper, Valleley, Polaha, Begeny, & Evans, 2006; Norlin, Crawford, Bell, Sheng, & Stein, 2011; Regalado, Larson, Wissow, & Halfon, 2010); and (c) integrating behavioral health services into medical settings increases patient access (Burt, Garbacz, Kupzyk, Frerichs, & Gathje, 2014; Kessler & Stafford, 2008), thereby improving patient experiences, reducing the cost of care, and promoting population health (Kazak, Nash, Hiroto, & Kaslow, 2017). Behavior analysts in particular have historically noted the potential of a mutually beneficial partnership with pediatrics (Cataldo, 1982; Christophersen & Rapoff, 1979).…”
mentioning
confidence: 99%
“…Pediatricians spend an average of 14 minutes with each patient (Ferris et al, 1998), which is hardly enough time to care for acute medical needs; screen for general medical issues; and provide basic preventive services, such as immunizations. Second, pediatricians have a training mandate to prioritize children's physical health and may not regard behavioral and developmental issues as within their range of expertise (Lavigne et al, 1998;Sharpe, Pantell, Murphy, <&. Lewis, 1992).…”
Section: Barriers To Psychosocial Services In Primary Carementioning
confidence: 99%
“…All pediatricians should have received training in children's behavior and development; however, their hands-on, clinical ex-posure varies. Some pediatricians are very competent dealing with these issues, whereas others are uncomfortable or unfamiliar with behavioral issues, particularly around sensitive ones, such as sexuality or substance use (Blum, 1987;Perrin, 1999;Sharpe et al, 1992). Although there are many systematic procedures for gathering information about children's behavior and development (Stancin & Palermo, 1997), these procedures are not routinely used in primary care.…”
Section: Barriers To Psychosocial Services In Primary Carementioning
confidence: 99%